Place attachment and the value of place in the life of the users - Ujang, Norsidah; Zakariya, Khalilah (Elsevier, 2015)
Place attachment is a form of connection between a person and the environmental setting. In the production of urban places, planners and designers mainly focus on the quality of the physical components. However, the aspects of meanings and attachment are not adequately considered in the planning and decision-making process. This study utilizes semi-structured interview method to examine place attachment dimensions in understanding the values of a place in the life of the users. Sample cases include examining attachment to streets in the city centre of Kuala Lumpur, Malaysia. It was evident that users’ roles and ethnic backgrounds influenced their responses. Attachment to the places was economically, socially and culturally oriented and prevalent in their daily experience of the places, and the place memories recalled.